Estimer les houles cycloniques à partir d’observations météorologiques limitées : exemple de la submersion d’Anaa en 1906 aux Tuamotu (Polynésie française) - Remy Canavesio (VertigO)
Hurricane swell submersion is the main natural hazard in the atolls of the Tuamotu archipelago. The analyze of recent hurricanes by high-resolution coupled models has improved the understanding of this hazard. Nevertheless, the knowledge of extreme swell events is faced to representativeness problem of the sample caused by the low frequency of hurricanes in French Polynesia. This paper offer a methodology to estimate the size of hurricane swell by analyzing basic weather observations at sea level. This method that is appealing to swell model simulations as well, give an opportunity to improve the knowledge of these hazards by the extending of the analyze to historic hurricanes (more than one century) through archives. The Anaa submersion in 1906 is examined in detail in order to prove the interest of this method in the scope of risk studies.